Intestinal epithelial Caspase-8 signaling is essential to prevent necroptosis during Salmonella Typhimurium induced enteritis - Hefele, Manuela; Stolzer, Iris; Ruder, Barbara; He, Gui-Wei; Mahapatro, Mousumi; Wirtz, Stefan; Neurath, Markus; Günther, Claudia (Mucosal Immunology, 2018)
Although induction of host cell death is a pivotal step during bacteria-induced gastroenteritis, the molecular regulation remains to be fully characterized. To expand our knowledge, we investigated the role of the central cell death regulator Caspase-8 in response to Salmonella Typhimurium. Here, we uncovered that intestinal salmonellosis was associated with strong upregulation of members of the host cell death machinery in intestinal epithelial cells (IECs) as an early event, suggesting that elimination of infected IECs represents a host defense strategy. Indeed, Casp8∆IEC mice displayed severe tissue damage and high lethality after infection. Additional deletion of Ripk3 or Mlkl rescued epithelial cell death and lethality of Casp8∆IEC mice, demonstrating the crucial role of Caspase-8 as a negative regulator of necroptosis. While Casp8∆IECTnfr1-/- mice showed improved survival after infection, tissue destruction was similar to Casp8∆IEC mice, indicating that necroptosis partially depends on TNF-α signaling. Although there was no impairment in antimicrobial peptide secretion during the early phase of infection, functional Caspase-8 seems to be required to control pathogen colonization. Collectively, these results demonstrate that Caspase-8 is essential to prevent Salmonella Typhimurium induced enteritis and to ensure host survival by two different mechanisms: maintenance of intestinal barrier function and restriction of pathogen colonization.
EVALuna2:35156